Un univers familial en changement - B.-Dandurand, Renée (Cahiers de recherche sociologique, 1990)
À partir du constat que la vie familiale a connu des transformations importantes depuis un quart de siècle, cet article cherche à répondre à deux questions : comment l’approche sociologique peut-elle appréhender de tels phénomènes? Quelle lecture faut-il privilégier pour bien en saisir la signification?
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; europe; famille; maternité; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Feminism/postmodernism - Nicholson, Linda J. (Thinking gender, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis